2022
DOI: 10.3233/bmr-200193
|View full text |Cite
|
Sign up to set email alerts
|

A single intraarticular platelet-rich plasma improves pain and function for patients with early knee osteoarthritis: Analyses by radiographic severity and age

Abstract: BACKGROUND: Most studies use platelet-rich plasma (PRP) requiring multiple intraarticular injections for knee osteoarthritis (OA). OBJECTIVE: To investigate the efficacy of a single intraarticular PRP injection for patients with early knee OA and consider subgroup analyses of radiographic severity and age, respectively. METHODS: Forty-one patients with knee OA (Kellgren-Lawrence grade 1–2) received a single PRP injection into the target knee and were assessed at baseline and 1, 3, and 6 months postinjection. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The effects of PRP on cell proliferation and ECM formation could lead to restoring cartilage damage in the early stages of OA. Recent evidence has suggested that PRP therapy is clinically more effective in patients with mild or moderate knee OA 73,74 . It is very difficult for PRP to restore the damage generated in the cartilage or synovium in people with more severe OA.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of PRP on cell proliferation and ECM formation could lead to restoring cartilage damage in the early stages of OA. Recent evidence has suggested that PRP therapy is clinically more effective in patients with mild or moderate knee OA 73,74 . It is very difficult for PRP to restore the damage generated in the cartilage or synovium in people with more severe OA.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al studied the effectiveness of a single intra-articular PRP injection for patients with early knee OA and considered subgroup analyses of radiographic severity and age [47]. Forty-one patients with knee OA (K/L grade 1-2) were given a single PRP injection into the knee and were evaluated at baseline and at 1, 3, and 6 months after injection.…”
Section: Case Seriesmentioning
confidence: 99%
“…Therefore, this study supported putting the one-injection regimen into clinical practice. However, Sun et al stated that further research is required for more definitive conclusions [47].…”
Section: Case Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 PRP appears to have no therapeutic effect when the degree of degeneration is severe. 2 , 3 , 4 , 5 , 6 , 7 However, consecutive leukocyte-rich PRP (LR-PRP) injections have been shown to have therapeutic effects, regardless of the degree of degeneration, 8 , 9 suggesting the benefits of consecutive LR-PRP injections for patients with severe knee degeneration.…”
Section: Introductionmentioning
confidence: 99%